2020
DOI: 10.26418/lkuntan.v2i3.34780
|View full text |Cite
|
Sign up to set email alerts
|

Isolasi dan karakterisasi Bakteri Asam Laktat (BAL) dari Ale-ale dan Cincalok

Abstract: Ale-ale dan cincalok merupakan produk makanan khas Kalimantan Barat yang diolah melalui proses fermentasi secara alami melibatkan Bakteri Asam Laktat (BAL). BAL dikategorikan sebagai foodgrade microorganism karena bersifat non-patogen dan aman bagi manusia, juga mempunyai peranan penting dalam fermentasi makanan daam pengaruh pengawetan dengan hasil peningkatan daya awet pada produk. Karakteristik BAL pada penelitian ini yaitu Gram positif, katalase negatif, mampu memfermentasi glukosa, negatif indol, mampu me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 1 publication
0
5
0
1
Order By: Relevance
“…A catalase test was carried out to determine the ability to produce catalase enzyme and isolate tolerance to oxygen. Catalase is an enzyme capable of catalyzing the direct conversion of hydrogen peroxide (H2O2), which is toxic to cells, into water and oxygen [17]. The chemical reaction produced by the catalysis of the enzyme catalase against H2O2 is: catalase 2 H2O2…”
Section: Catalase Testmentioning
confidence: 99%
“…A catalase test was carried out to determine the ability to produce catalase enzyme and isolate tolerance to oxygen. Catalase is an enzyme capable of catalyzing the direct conversion of hydrogen peroxide (H2O2), which is toxic to cells, into water and oxygen [17]. The chemical reaction produced by the catalysis of the enzyme catalase against H2O2 is: catalase 2 H2O2…”
Section: Catalase Testmentioning
confidence: 99%
“…This indicated the bacterial isolates could break down H 2 O 2 and produce oxygen gas. Based on Nurhamidah et al 12 , positive catalase is indicated by the presence of air bubbles in the isolate, indicating the presence of the catalase enzyme produced by bacteria that can convert hydrogen peroxide into water and oxygen. According to Holt et al 13 BAL is catalase negative.…”
Section: Bacterial Physiologymentioning
confidence: 99%
“…Some bacteria ferment glucose and produce various acidic products that will lower the pH of the growth medium to 5 or lower. Adding a pH indicator methyl red can show a change in pH to acid 12 .…”
Section: Bacterial Physiologymentioning
confidence: 99%
“…The film (Figure 2c) has similar characteristics to fragments, irregular, but its color is transparent. The type of fiber (Figure 2d) is a type of microplastic such as thin fibers that easily accumulate in sediments [7]. Based on the Figure 3, the fragment type is known to have the highest average abundance both in waters (4,4 × 10 6 particles/km 2 ) and sediments (7,6 × 10 8 partikel/km 2 ).…”
Section: Types Of Microplasctics Found In Surabaya Mangrove Areasmentioning
confidence: 99%